PENGARUH KECERDASAN EMOSIONAL TERHADAP KOMITMEN ORGANISASI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PEGAWAI PUSKESMAS MEURAXA KOTA BANDA ACEH - Nizhami, Muhammad Farhan; Gadeng, Tarmizi; Murad, Suryani (An Nuqud Journal of Islamic Economics, 2025)
The purpose of this study is to examine and analyze the effect of Emotional Intelligence on Organizational Commitment through Job Satisfaction among employees at Meuraxa Health Center, Banda Aceh City. The sample size of this study consists of 42 respondents. Data were collected through questionnaires and documentation study. Data processing was conducted using quantitative data analysis techniques. Statistical tools used to test the functional relationship between dependent variables (bound variables) and independent variables (free variables) are path analysis at a 95% Job Satisfaction level. The results show that Emotional Intelligence has an effect on Organizational Commitment at Meuraxa Health Center, Banda Aceh City. Emotional Intelligence directly affects Job Satisfaction among employees at Meuraxa Health Center, Banda Aceh City. Job Satisfaction significantly affects Organizational Commitment among employees at Meuraxa Health Center, Banda Aceh City. Emotional Intelligence significantly affects Organizational Commitment at Meuraxa Health Center, Banda Aceh City through Job Satisfaction as a mediating variable. Partially, the direct effect of Emotional Intelligence on Organizational Commitment is greater than the indirect effect of Emotional Intelligence on Organizational Commitment mediated by Job Satisfaction. The implication of this research is that emotional intelligence can enhance emotional intelligence through job satisfaction. Employees with high emotional intelligence can manage negative emotions more effectively, so they are less likely to feel stressed or pressured at work.